2011
DOI: 10.1097/aln.0b013e318221fcc9
|View full text |Cite
|
Sign up to set email alerts
|

Perineural Dexmedetomidine Added to Ropivacaine for Sciatic Nerve Block in Rats Prolongs the Duration of Analgesia by Blocking the Hyperpolarization-activated Cation Current

Abstract: Background The present study was designed to test the hypothesis that the increased duration of analgesia caused by adding dexmedetomidine to local anesthetic results from blockade of the hyperpolarization-activated cation (Ih)current. Methods In this randomized, blinded, controlled study, the analgesic effects of peripheral nerve blocks using 0.5% ropivacaine alone or 0.5% ropivacaine plus dexmedetomidine (34 μM or 6 μg/kg) were assessed with or without the pretreatment of α1- and α2-adrenoceptor antagonist… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

8
233
0
5

Year Published

2013
2013
2021
2021

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 269 publications
(255 citation statements)
references
References 33 publications
(66 reference statements)
8
233
0
5
Order By: Relevance
“…Kousugi et al in their study found high concentrations of dexmedetomidine inhibit compound action potentials in frog sciatic nerves without α-2 adrenorecptors activation in a concentration dependent manner and reversibly. [23,24,25] The efficacy of perineural dexmedetomidine for analgesia has been established. This effect is dose dependent and the effect is peripheral (not caused by centrally mediated or systemic analgesia).…”
Section: Discussionmentioning
confidence: 99%
“…Kousugi et al in their study found high concentrations of dexmedetomidine inhibit compound action potentials in frog sciatic nerves without α-2 adrenorecptors activation in a concentration dependent manner and reversibly. [23,24,25] The efficacy of perineural dexmedetomidine for analgesia has been established. This effect is dose dependent and the effect is peripheral (not caused by centrally mediated or systemic analgesia).…”
Section: Discussionmentioning
confidence: 99%
“…Ishii and colleagues reported that dexmedetomidine induced activation of K + -channels through α 2A -and α 2C -adrenoceptors results in hyperpolarization of substantia gelatinosa neurons 15 . Similarly, Brummett and colleagues reported that dexmedetomidine's antinociceptive action depends on inhibiting the build up of excitation via hyperpolarization-activated cation current (I h ) and is reversed by I h agonist forskolin 17 . Among spinal catheterization methods, sacral approach is mainly suited for epidural drug administration and lumbar approach carries the risks of bone damage and infl ammation due to fi xatives.…”
Section: Discussionmentioning
confidence: 99%
“…It produces a dose dependent sedation and analgesia, recently, Dexmedetomidine has been used as adjuvant to LA drugs in peripheral nerve block and eye block [41] this action is mainly due to blocking the hyperpolarization-activated cation current [42].…”
Section: Discussionmentioning
confidence: 99%